Can invasive interventions be avoided with a holistic swallowing therapy program in older patients in intensive care units: percutaneous endoscopic gastrostomy tubes or oral intake? - Eliküçük, Çağla; Esen Aydinli, Fatma; Has Selmi, Nazan; Uzunoğlu, Cansu; Köksal, Murathan; Öter, Volkan; Akan, Belgin; Bostanci, Erdal Birol; Argun, Güldeniz (Frontiers in Neurology, 2025)
IntroductionThe use of percutaneous endoscopic gastrostomy (PEG) tubes in older patients did not show any benefits in terms of survival, improvement in quality of life, or reduction in aspiration pneumonia. Significant gaps exist regarding the evidence for the evaluation and management of dysphagia in older patients. This study aimed to diagnose swallowing disorders and highlight the importance of swallowing therapy in older patients in intensive care units (ICUs).Materials and methodsTwenty-five older patients (12 men, 13 women, mean age 67.22 ± 24.03 years) hospitalized in the ICUs with complaints of dysphagia were analyzed prospectively. The 12 weeks (14−16 sessions) of swallowing therapy were administered to patients with dysphagia who signed the (voluntary) consent form. The bedside water swallowing test (BWSS), Functional Oral Intake Scale (FOIS) Score, Clinical Swallowing Evaluation, Mini Nutritional Assessment Test (MNAT), Eating Assessment Tool (EAT-10), the Turkish version of the World Health Organisation Quality of Life Scale Elderly Module, and the Swallowing Therapy Programme Protocol were applied. Pretherapy stage (T1) and post-therapy stage (T2) results were compared with videofluoroscopy swallowing study (VFSS) recordings with thin liquids, moderately thick liquids, extremely thick liquids, and crackers (International Dysphagia Diet Standardization Initiative [IDDSI] Levels 0, 3, 4, and 7, respectively).ResultsThe World Health Organisation Quality of Life Scale Elderly Module (WHOQOL-OLD) raw scores significantly improved from T1 (38.63 ± 7.05) to T2 (73.07 ± 4.82). The bedside water swallowing test results demonstrated statistically significant differences in therapy timings among older patients (p < 0.001). There were significant improvements in swallowing physiology, as represented by the improved oral and pharyngeal composite scores of the Modified Barium Swallow Impairment Profile (MBSImP) and Penetration-Aspiration Scala (PAS) levels. Before therapy, all patients exhibited high rates of oropharyngeal residue with thin liquids and spoon-thick pudding viscosities (MNA ≤ 17). The results reported in the present study show that malnutrition risk is linked to a poorer QoL in older patients on admission to ICUs. Statistical analyses revealed the dominant effects of functional status and eating-related factors on QoL in this group.DiscussionEarly dysphagia diagnosis of older patients and subsequent application of exercise-based swallowing therapy increase the quality of life of patients. In this study, exercise-based swallowing therapy was developed in Turkey and can be used in older patients as part of a holistic cognitive-communication-swallowing intervention program. Results prove the effectiveness of the developed exercise-based swallowing therapy on the cognitive-communication-swallowing skills of older patients. The present findings reinforce the role of nutrition as a priority for improving patients’ perceptions of QoL. Further studies are required to investigate and identify the interventions that improve QoL in older patients. More studies with better research designs are required to establish whether nutritional intervention is effective in enhancing QoL in this vulnerable group.